Inhibition of Aβ Aggregation by Cholesterol-End-Modified PEG Vesicles and Micelles - Shota Watanabe; Motoki Ueda; Shoichiro Asayama (Pharmaceutics)
Background/Objectives: This study aimed to design and evaluate Chol-PEG2000 micelles and Chol-PEG500 vesicles as drug delivery system (DDS) carriers and inhibitors of amyloid-β (Aβ) aggregation, a key factor in Alzheimer’s disease (AD). Methods: The physical properties of Chol-PEG assemblies were characterized using dynamic light scattering (DLS), electrophoretic light scattering (ELS), and transmission electron microscopy (TEM). Inhibitory effects on Aβ aggregation were assessed via thioflavin T (ThT) assay, circular dichroism (CD) spectroscopy, and native polyacrylamide gel electrophoresis (native-PAGE). Results: Chol-PEG2000 micelles and Chol-PEG500 vesicles were found to exhibit diameters of 20–30 nm and 70–80 nm, respectively, with neutral surface charges and those physical properties indicated the high affinity for Aβ. At a 10-fold molar ratio, thioflavin T (ThT) assay revealed that Chol-PEG2000 delayed Aβ fibril elongation by 20 hours, while Chol-PEG500 delayed it by 40 hours against Aβ peptide. At a 50-fold molar ratio, both Chol-PEG2000 and Chol-PEG500 significantly inhibited Aβ aggregation, as indicated by minimal fluorescence intensity increases over 48 hours. CD spectroscopy indicated that Aβ maintained its random coil structure in the presence of Chol-PEG assemblies at a 50-fold molar ratio. Native-PAGE analysis demonstrated a retardation in Aβ migration immediately after mixing with Chol-PEG assemblies, suggesting complex formation. However, this retardation disappeared within 5 min, implying rapid dissociation of the complexes. Conclusions: This study demonstrated that Chol-PEG500 vesicles more effectively inhibit Aβ aggregation than Chol-PEG2000 micelles. Chol-PEG assemblies perform as DDS carriers to be capable of inhibiting Aβ aggregation. Chol-PEG assemblies can deliver additional therapeutics targeting other aspects of AD pathology. This dual-function platform shows promise as both a DDS carrier and a therapeutic agent, potentially contributing to a fundamental cure for AD.